Theoretical Aspects of Professional Competence of Police Officers from the Tactical and Operative Response Unit (Law and Safety, 2021)
In this article the author has made a theoretical analysis of law enforcement officials’ professional competence and has defined the meaning of professional competence of the police officer in the tactical-operational respond unit (TOR) of the National Police of Ukraine. Taking into consideration specific official tasks and professional activity the author describes the main abilities of the police unit (TOR). Among the structural components of professional competence of the police unit TOR: personal, active, social competence is separated. It is shown the intentional filling of structural ingredients of the professional competence of the police unit TOR. It is underlined that the actuality of the research of the development of police officers’ professional competence in this tactical-operational respond unit is connected with the increasing of citizens’ “close” looks at the police actions on the whole and a new-organized unit of the patrol police especially.   Social-economic and political changes which are taking place in the lives of modern Ukrainians are characterized by the considerable increase of their civil activity and are expressed by their participation in public events of the different types: political, economic, social, sports, cultural, gendered, religious, ecological and so on. Considering Ukrainians’ high political activity, the urgent necessity of security guaranteeing and holding the public order were formed by the National Police Bodies during public events with participation of a great number of people. That’s why on purpose of providing civil security and law-and-order guard of the public events in 2017 the new unit of patrol police of tactical-operational respond TOR was organized. The new challenges have arisen before the new-organized police unit [3, 6]: to minimize the risks which may appear during public events; to decrease tense in the crowd without demonstrating force; to prevent and to resist street criminality; to be on patrol in the city for the operational support of the patrol police crews in the case of calls with the higher degree of the risk; to react on the situations where there is a real threat of using the weapon or another threat to people’s life; to detain people who are hiding from justice or are wanted and can be dangerous. “We need the units of the civil guard with a new mentality, and absolutely a new approach”, said the assistant of the minister of MIA of Ukraine S. Yarovyi in his interview [3].   The fulfillment of the mentioned tasks demands from the policemen a high level of preparation and professional competence, which is expressed according to O. Tsylmak in the person’s possibility to use the set of acquired knowledge, skills and abilities in practical professional activity effectively [11]. The actuality of the research of the development of professional competence of a police officer in the tactical –operational respond unit is connected with the increasing of people’s “close” looks at the policemen in general and the new-organized patrol police unit in particular. The question of the policeman’s professional competence is a central one because nowadays in the communication with the policemen people use technical means of fixation (such as photo-, video-fixation), somebody to protect themselves against the police misconduct, somebody to show policemen “in not the most flattering light”.
Keywords: professional competence; a police officer; patrol; tactical and operative response.